Integrated Chinese and Western medicine for stable angina pectoris of coronary heart disease: a real-world study including 690 patients - Yu, Linghua; Wang, Zihan; Xu, Chenxi; Liu, Anxiang; Li, Tong; Wang, Yubi; Lu, Xiaoyan; Xu, Hao (Frontiers in Cardiovascular Medicine, 2023)
Objective We aimed to evaluate the effects of integrated Chinese and Western medical therapeutic modalities on clinical prognosis in a population with stable angina pectoris (SAP) of coronary heart disease (CHD). Methods In a prospective cohort study, 732 patients with SAP of CHD hospitalized in the Integrated Cardiology Unit of the China-Japan Friendship Hospital From October 2020 to October 2021 were included. The patients were divided into integrated treatment and conventional treatment groups according to whether they had been taking Chinese medicine for more than 6 months per year. The occurrence of composite cardiovascular events (CVEs), including cardiac death, non-fatal myocardial infarction, revascularization, stroke, all-cause death, and readmission due to angina attack, heart failure, or malignant arrhythmia, was recorded during follow-up. The effects of different treatment modalities on prognosis were evaluated using univariate and multifactorial logistic regression. Logistic regression models were evaluated using receiver operating characteristic (ROC) curves. In sensitivity analysis, the correlation between treatment modality and outcome events was corrected by rematching the two groups of patients using the propensity score matching (PSM) method. Results The data from 690 patients were included in the analysis, with 327 patients in the integrated treatment group and 363 patients in the conventional treatment group. CVEs occurred in 19 patients (5.8%) in the integrated treatment group and 37 patients (10.2%) in the conventional treatment group. The proportion of outcome events was significantly lower in the combination treatment group than in the conventional treatment group (P = 0.037). Covariate correction by multimodal multifactorial logistic regression revealed a lower risk of CVEs in patients receiving integrated therapy compared with conventional therapy (OR = 0.246, 95% CI = 0.097–0.622, P = 0.003). Moreover, a history of renal insufficiency (OR = 3.991, 95% CI = 1.164–13.684, P = 0.028) and a higher Gensini score (OR = 1.039, 95% CI = 1.028–1.050, P < 0.001) were risk factors for the development of CVEs. Model evaluation showed that C-statistic = 0.955 and area under the ROC curve (AUC) = 0.955. After PSM correction, the results still showed that integrated Chinese and Western medical treatment reduced the occurrence of CVEs in patients compared with Western treatment alone (OR = 0.339, 95% CI = 0.131–0.874, P = 0.025). Conclusion Integrated treatment based on Chinese and Western medicine might improve the prognosis and reduce the risk of CVEs in this disease population. Trial registration China Clinical Trials Registry, ChiCTR1800017891, Registered 20 August 2018, http://www.chictr.org.cn/showproj.aspx?proj = 30170.